Dedollarization in Liberia-Lessons From Cross-Country Experience - Menkulasi, Jeta (IMF Working Papers; Working Paper ;, 2009)
Liberia's experience with a dual currency regime, with the U.S. dollar enjoying legal tender status, dates to its founding as a sovereign country in 1847. Following the end of the most recent episode of civil war in late-2003, the new government has expressed interest in strengthening the role of the Liberian dollar. Liberia, however, is heavily dollarized, with the U.S. dollar estimated to account for about 90 percent of money supply. Cross-country experience suggests that dollarization does not preclude monetary policy from achieving its primary objective of price stability, and that successful and lasting dedollarization may be difficult to achieve.